The taxonomy of "digital health interventions" and their subgroups in the therapeutic rehabilitation of stroke patients - A scoping review / Die Taxonomie der "digitalen Gesundheitsinterventionen" und ihrer Untergruppen in der therapeutischen Schlaganfallrehabilitation - Ein Scoping Review - Stangenberg-Gliss Kirsten; Elser Alexander; Borgetto Bernhard Maria (Sciendo, 2023)
Stroke is a leading cause of impairment and death. Many survivors suffer from motor, sensory and speech impairments and require ongoing rehabilitation. Digital health interventions have the potential to overcome barriers such as distance between patient and therapist. However, there is a lack of clarity in terms and definitions used in research and practice. Therefore, the aim of this scoping review is to provide a comprehensive overview of the definitions and terms used in publications by healthcare professionals (occupational therapy, physiotherapy, speech and language therapy) related to digital stroke rehabilitation.